(untitled) (Surkhet Journal, 2025)
This study explores the issues and challenges associated with the integration of Information and Communication Technology (ICT) in both government and non government schools in Nepal. With the increasing emphasis on digital education, ICT has become a crucial component for enhancing teaching-learning processes and bridging educational gaps. Despite the government’s efforts to promote ICT in schools, disparities in implementation persist, particularly between public and private institutions. Using a mixed-methods approach, data were collected from 14 secondary schools; seven governments and seven non-governments, through surveys and interviews with headteachers and ICT teachers. The findings reveal that non-government schools have better ICT infrastructure, trained personnel, administrative support, and student access compared to their government counterparts. Government schools face multiple challenges such as insufficient devices, lack of training, poor internet connectivity, inadequate maintenance, and limited policy enforcement. Attitudinal resistance, language barriers, and socio cultural factors further hinder effective ICT integration. The study concludes that while ICT has the potential to transform education, a coordinated approach involving infrastructure development, teacher capacity building, localized content creation, and strong policy support is essential. These findings offer valuable insights for educational policymakers, school administrators, and stakeholders aiming to promote equitable and effective ICT implementation across all types of schools in Nepal.